Jews and Christians - parting ways in the first two centuries CE? reflections on the gains and losses of a model - Jews and Christians: parting ways in the first two centuries C.E.? Reflections on the gains and losses of a model 2019 Berlin; Schröter, Jens 1961-; Edsall, Benjamin A. 1982-; Verheyden, Joseph 1957-; Walter de Gruyter GmbH & Co. KG (Berlin Boston De Gruyter, 2021)
Frontmatter -- Table of Contents -- Introduction -- From “Wide and Narrow Way” to “The Ways that Never Parted”? Road Metaphors in Models of Jewish-Christian Relations in Antiquity -- What Never Belonged Together Cannot Part: Rethinking the So-Called Parting of the Ways between Judaism and Christianity -- Ioudaismos, Christianismos and the Parting of the Ways -- Was Paul a Jew Within Judaism? The Apostle to the Gentiles and His Communities in Their Historical Context -- Matthew within or outside of Judaism? From the ‘Parting of the Ways’ Model to a Multifaceted Approach -- Character and Conflict: Who Parts Company in Acts? -- “John within Judaism?” Textual, Historical, and Hermeneutical Considerations -- The Epistle of Barnabas, Jews and Christians -- Justin Martyr without the “Parting” or the “Ways” -- Beyond “The Parting of the Ways” between Jews and Christians in Asia Minor to a Model of Variegated Interaction -- Living Apart Together: Jews and Christians in Second-Century Rome – Re-visiting Some of the Actors Involved -- Jews and Christians? Sketches from Second Century Alexandria -- List of Contributors -- Index of Ancient Sources -- Index of Modern Authors -- Index of Subjects
The present volume is based on a conference held in October 2019 at the Faculty of Theology of Humboldt University Berlin as part of a common project of the Australian Catholic University, the Katholieke Universiteit Leuven and the Humboldt University Berlin. The aim is to discuss the relationships of “Jews” and “Christians” in the first two centuries CE against the background of recent debates which have called into question the image of “parting ways” for a description of the relationships of Judaism and Christianity in antiquity. One objection raised against this metaphor is that it accentuates differences at the expense of commonalities. Another critique is that this image looks from a later perspective at historical developments which can hardly be grasped with such a metaphor. It is more likely that distinctions between Jews, Christians, Jewish Christians, Christian Jews etc. are more blurred than the image of “parting ways” allows. In light of these considerations the contributions in this volume discuss the cogency of the “parting of the ways”-model with a look at prominent early Christian writers and places and suggest more appropriate metaphors to describe the relationships of Jews and Christians in the early period
Mode of access: Internet via World Wide Web.
Mit deutschen Zusammenfassungen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: RELIGION / Biblical Criticism & Interpretation / New Testament; Jewish Christianity; Jewish traditions in Early Christianity; Jews and Christians; Parting of the Ways; Konferenzschrift -- 2019 -- Berlin